When Chatbots Feel Human: How Anthropomorphism Shapes Consumer Satisfaction, Trust, and Loyalty in AI-Driven Brand Interactions - Albarq, Abbas N; Aljaafari, Abdullah Ibrahim; Mabkhot, Hashed; Alsuwaidan, Mohammed Samir (Journal of Cultural Analysis and Social Change, 2025)
This study investigates how chatbot anthropomorphism influences consumer satisfaction, trust, loyalty, and decision-making in AI-enabled brand interactions. Data were collected from 663 Saudi consumers through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Model assessment employed path coefficients, explanatory power (R²), and effect size (f²) to evaluate the robustness of hypothesized relationships. Findings reveal that anthropomorphic design significantly enhances satisfaction (β = 0.62, p < 0.001), trust (β = 0.57, p < 0.001), and loyalty (β = 0.48, p < 0.001), which subsequently mediate its effect on purchase decision-making. Although the direct effect of anthropomorphism on decision-making is marginal, the mediating role of engagement constructs considerably strengthens this association. The model demonstrated strong explanatory power (R² values 0.58–0.69), highlighting the strategic relevance of anthropomorphic cues in shaping consumer attitudes and behavioral intentions. The results contribute to AI-driven marketing literature by showing how anthropomorphism transforms chatbots into relational actors, enhancing trust, loyalty, and purchase intention. Beyond theoretical implications, the findings provide actionable insights for firms seeking to leverage human-like chatbot features as a relational strategy to improve consumer engagement and drive decision-making.